Mao's road to power : revolutionary writings, 1912-49.: revolutionary writings, 1912-49. From the Jinggangshan to the establishment of the Jiangxi Soviet, July 1927-December 1930 / Vol. 3, (2015) - Mao, Zedong, 1893-1976
No abstract available